Collaborative activities and library indoor environmental quality affecting performance, health, and well‐being of different library user groups in higher education. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to identify different indoor environmental quality (IEQ) criteria affecting performance, health, and well‐being of library user groups in higher education. The study investigated the differences in significant IEQ criteria affecting the performance, health, and well‐being among the library user groups conducting certain types of collaborative activities. The aim was to was to find the significant IEQ criteria particular to each group conducting certain types of collaborative activities.Design/methodology/approach – Four types of collaborative activities were categorized based on the organizational knowledge creation theory in the knowledge management field. A total of ten IEQ criteria affecting performance, health, and well‐being were identified based on a literature review of other studies and existing instruments. A survey was conducted via online with library users in a higher education library on the east coast of the USA. Responses from a total of 421 students were analyzed by descriptive statistics and analysis of variance statistics.Findings – The results indicated that the group conducting only individual focused work and socializing in a group showed statistically lower significance in acoustics, privacy, and ergonomics furniture than one or more of the other groups. The group conducting all four collaborative activities exhibited statistically higher significance in ergonomic furniture and aesthetics than one or more of the other groups.Originality/value – The study provides a comprehensive framework to be used in occupant survey to measure occupant performance, health, and well‐being. It also offers practical implications for enhancing particular IEQ criteria for each library user group conducting certain types of collaborative activities in the academic library of higher education.